Role of a world-wide company in changes of industrial space of Poland in the transformation period, with special reference to the Coca-Cola Company - Tkocz, Maria; Żydzik, Jakub (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2010)
The Coca-Cola Company, a producer of soft drinks, the largest in the world and also in Poland, started its production in Poland in 1992. The first factory was based in Radzymin near Warsaw and in the beginning it employed 200 workers. It was the first direct investment of the Company, which initiated subsequent investments connected with setting up new factories and gradual development of distribution network. At present, in the Polish market the Coca-Cola Company employs over 3500 workers and owns three modern factories located in Staniątki near Niepołomice, Łódź and Radzymin, and also a bottling plant in Tylicz. Moreover, its distribution and sale network is recognized as one of the most advanced in the Polish market. About 980 market and sale specialists are employed in 35 local sale centres, situated in the largest towns of the subregions. As a result of its investments and financial expenditures during the last two decades, the Coca-Cola Company has significantly influenced the employment structure, and simultaneously, it has become a significant element of food industry in Poland. A key strategy and the primary aim of the Company is creation of an international team which would let the largest world-wide brand become a global brand. Taking into account this assumption and the performance of the Coca-Cola Company in the Polish market, it may be assumed that the aim of the Company is accomplished and its further development may result in further changes in the economic space of Poland.